Evaluation of genetic polymorphism of proteins in stellate sturgeon Acipenser stellatus (Pall) in aquaculture with reference to economically valuable traits. Issue 3 (December 2021) - Shishanova, Elena; Shishanov, Grigory; Isaev, Dmitry
Abstract: One of the main goals of sturgeon aquaculture is the restoration and renewal of wild populations of sturgeon fish in nature, which creates a tension between selective breeding with maintenance of valuable economic traits in a homozygous state and the need to conserve genetic diversity ensuring fitness in natural environments. It is generally assumed that important economic characteristics, such as body weight and size, growth rate, fecundity, etc., as well as fitness in fish, are associated with heterozygosity and genetic polymorphism of some key metabolic enzymes. It remains unclear whether aquaculture conditions can be as a whole selection factor in favor of certain allelic variants of these enzymes. To establish the relationship between some economic traits and enzymatic polymorphism, we studied the distribution of allelic variants of LDH-3, AAT-2, FGM, and Est enzymes in stellate sturgeon reared in aquaculture. We revealed a frequency bias of some allelic variants of the studied enzymes in a cohort of fish from the generation bred in aquaculture compared to the frequencies of those alleles in wild natural populations. Our study suggests that industrial breeding promotes selection in the direction of reducing size but increasing survival rates, which correlates with certain allelic variants.